Immunomodulatory Effects of Synbiotic Lactic Acid Bacteria from Dangke and Inulin from Dahlia Tubers - Ayu Febriani; Hafsan Hafsan; St Aisyah Sijid; Fatmawati Nur; Cut Muthiadin; Faten Khudaer (Al Jahiz, 2025)
Synbiotics, the synergistic combination of probiotics and prebiotics, have attracted growing scientific interest due to their potential to modulate immune responses. However, the immunomodulatory effects of synbiotics derived from traditional foods remain underexplored. This study aimed to evaluate the immune-enhancing potential of synbiotics formulated from Lactobacillus fermentum isolated from Dangke (a traditional South Sulawesi cheese) and inulin extracted from Dahlia tubers. The novelty of this work lies in the utilization of culturally unique, locally sourced microbial and prebiotic components that have not previously been tested for immunological impact. A total of 28 mice were randomly divided into four groups: one negative control group (P0) and three treatment groups (P1, P2, P3) receiving different doses of synbiotics over a 20-day treatment period. Parameters observed included changes in body weight, macrophage phagocytosis activity, and organ indices (liver and spleen). Results showed that mice in P1 and P2 groups exhibited significant increases in body weight (P1: +12.5%, P2: +15.3%, p < 0.05) compared to the control. Moreover, macrophage phagocytic activity was markedly improved in the treatment groups (p < 0.01). Liver and spleen indices were also significantly elevated (p < 0.05), indicating enhanced organ function. These findings suggest that synbiotics containing L. fermentum and Dahlia inulin have promising immunomodulatory effects, highlighting their potential for development as novel functional food ingredients with health-promoting benefits.